AI and the Exercise of Judicial Authority, Ex Machina - Beata Stępień-Załucka (Ediciones Laborum, 2025)
Beata Stępień Załucka is a legal practitioner and an academic with the status of a university professor specialising in the promotion and protection of human rights, constitutional law and LegalTech. She is currently Head of the Department of Human Rights at the Faculty of Law and Administration of the University of Rzeszow [Poland] and also practices as a lawyer (advocate). She also has experience of academic work in other units, including long-term scientific internships in Poland and abroad (including University of Reggio Calabria [Italy], Universidad de la Laguna [Spain], Universidad de Las Palmas de Gran Canaria [Spain], University of Pitesti [Romania], Rutgers University [USA], Sulkhan-Saba Orbeliani University [Georgia]). She is a member of the Instituto Iberoamericano de Estudios Juridicos [Portugal], Medditeranea International Center for Human Rights Research [Italy] and EUROFUR European Research Group. The book is the result of collaboration within a research group ‘Judicial decision making. Special consideration of the migratory phenomenon'(LDJC; GIR 261) conducted at the Universidad de Las Palmas de Gran Canaria, led by Prof. Laura Miraut Martín. The subject of the study is the use of artificial intelligence in the judiciary, with particular emphasis on judicial decision-making. The author considers the constitutional standards of judicial authority, referring, among other things, to AI's compliance with the requirements of the right to a fair trial. The study presents selected AI-based solutions found in judicial practice, attempting to set a standard for the use of algorithms in the judiciary, and considering the future of artificial courts.